Assessment of conjugal vigilance and distress in relation to mental health - WACIBA , William WILONDJA; Masumbuko, Robert Nongo; Kitoko, Patient Masumbuko (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
In the Democratic Republic of Congo (DRC), the domestic violence remains a phenomenon forgothen, for decades, given its insidous nature under-reporting during surveys and the cultural influence in the lives of couples. Thus, this study makes it possible to evaluate conjugal violence, to understand the indicators of marital distress and to establish the relationship between marital distress and the mental thealth of the couples.